Peripheral alveolar nitric oxide concentration reflects alveolar inflammation in autoimmune pulmonary alveolar proteinosis. Issue 1 (23rd March 2018) - Hirano, Taizou; Ohkouchi, Shinya; Tode, Naoki; Kobayashi, Makoto; Ono, Manabu; Satoh, Teruyuki; Mitsuishi, Yoichiro; Watanabe, Akira; Tabata, Masao; Irokawa, Toshiya; Ogawa, Hiromasa; Sugiura, Hisatoshi; et al.
Autoimmune pulmonary alveolar proteinosis (aPAP) is caused by an excess of autoantibodies against granulocyte-macrophage colony-stimulating factor (GM-CSF). In this situation, the clearance of intracellular debris in alveolar macrophages is impaired, and the alveolar spaces are occupied by excessive surfactant sediments. Several serum markers (lactate dehydrogenase (LDH), KL-6, carcinoembryonic antigen and surfactant protein D), alveolar–arterial oxygen difference ( P A–aO2 ) and the percentage diffusing capacity of the lung for carbon monoxide (% D LCO ) have a correlation with the disease severity and are used to evaluate the severity of aPAP [1]. Nitric oxide and alveolar macrophage inflammation http://ow.ly/czCx30i12n8